THE NIGHT MANAGER - Carre, John Le, 1931- author (New York, : Ballantine Books, 1993)
Jonathan Pine is taking refuge from his demands as a night manager in a luxury hotel, until the day he agrees to stand up and be counted in the fight against a heart of darkness, the unholy alliance between the intelligence community and the secret arms trade. From the cliffs of west Cornwall via the Caribbean to post-Noriega Panana, Pine chases his quarry - the worst man in the world.